What Drives Faculty to Volunteer at a Student-Run Clinic for the Underserved? - Rubenstein, William; Rifkin, Robert; Huber, Brianne; Pedowitz, Elizabeth; Rabkin, Jacqui; Thomas, David; Meah, Yasmin (Journal of Student-Run Clinics, 2016)
Background: It is estimated that more than half of all US medical schools operate at least one student-run clinic (SRC). These clinics provide care to vulnerable communities and allow students to learn about systems-based practice while improving their clinical skills. All SRCs are supervised by faculty physicians who oversee clinical care while providing ethical and professional guidance to the students. Because an SRC cannot operate without physician volunteers, physician recruitment and retention are important considerations for the student clinic organizers. This study aimed to identify the key factors that promote robust physician engagement in SRCs. Methods: Between January 2012 and March 2015, the East Harlem Health Outreach Partnership (EHHOP), an SRC, administered weekly online surveys to the physicians who volunteered at clinic that week. The survey consisted of ten questions assessing the overall volunteer experience, the competence of the student volunteers, and the clinic flow. Results were compiled and categorized with any answer given three or more times included in the results. Results: Forty-five surveys were completed and included in the analysis. The top reasons for volunteering at the SRC include working with and teaching students, serving a vulnerable population, and the ease of precepting in a well-managed clinic. Fewer respondents indicated that additional incentives would make them more likely to volunteer. Conclusions: The findings suggest that recruiting talented, motivated students and maintaining an efficiently-run clinic – as opposed to providing external incentives – may be the best approach to increasing physician recruitment at SRCs.